Answer:
The number is 10
Step-by-step explanation:
Let the number be x.
four thirds times = 4/3
According to the statement:
four thrids times the sum of a number and 8 is 24
4/3 *(x+8)= 24
Move 3 to the R.H.S and Multiply 4 with the parenthesis.
4x+32=24*3
4x+32=72
Move constant to the R.H.S
4x=72-32
4x=40
Divide both the terms by 4
4x/4=40/4
x=10
Therefore the number is 10....
Final answer:
To solve the equation, which is four thirds times the sum of a number and 8 equals 24, we isolate the variable by dividing by four thirds and subtracting 8 from both sides, resulting in the number being 10.
Explanation:
The student's question is asking to solve an algebraic equation. Specifically, the equation is: four thirds times the sum of a number and 8 equals 24. To find the number, represented by a variable, we'll denote it as x and translate the statement into the following equation: (4/3) × (x + 8) = 24.
First, we need to divide both sides of the equation by 4/3 to isolate the sum on one side:
(x + 8) = 24 × (3/4)
(x + 8) = 18
Now, subtract 8 from both sides to solve for x:
x = 18 - 8
x = 10
The final answer is that the number is 10. This is obtained through a step-by-step explanation solving the initial equation.
A 12-inch board is cut into sections that are 3/4 inches long each. How many sections can you make?
Answer:
16
Step-by-step explanation:
If you have a 12-inch board and you are making 3/4 inch long sections, and you want to know many times you can do that here.
You just need to take 12 and divide it by the 3/4, to see how many sections you can have.
[tex]12 \div \frac{3}{4}[/tex]
Change division to multiplication by taking the reciprocal (the flipping) of the second number:
[tex]12 \cdot \frac{4}{3}[/tex]
Write 12 as a fraction:
[tex]\frac{12}{1}\cdot \frac{4}{3}[/tex]
To multiply fractions, multiply straight across on top and straight across on bottom:
[tex]\frac{(12)(4)}{(1)(3)}[/tex]
[tex]\frac{48}{3}[/tex]
16
Final answer:
By dividing the 12-inch board length by the section length of 3/4 inches, we find that 16 sections can be made.
Explanation:
The question asks how many sections of 3/4 inches can be made from a 12-inch board. To find this, divide the total length of the board by the length of each section. Calculate by dividing 12 inches by 3/4 inches (which is the same as 12 divided by 0.75 in decimal form).
Convert the fraction 3/4 to decimal: 3 ÷ 4 = 0.75.Divide the total length of the board by the length of one section: 12 ÷ 0.75 = 16.Therefore, you can cut 16 sections that are 3/4 inches long each from a 12-inch board.
use the difference of squares identity to write this polynomial in factored form 9x²-49
[tex]\bf 9x^2-49\implies 3^2x^2-7^2\implies \stackrel{\stackrel{\textit{difference of}}{\textit{squares}}}{(3x)^2-7^2}\implies (3x-7)(3x+7)[/tex]
Find the value when x=2 and y=3 2x^0y^-2
Answer:
54
Step-by-step explanation:
2x^0y^-2
Let x =2 and y =3
2 * (2)^0 3^(3)
2 to the zero power is 1
2 * 1 *27
54
Answer:The answer is 1/9!
Step-by-step explanation:
Have a good day!
what is the value of y in the solution to the system of equations? 1/3x + 1/4y = 1 2x-3y=-30
Answer:
y = 8Step-by-step explanation:
[tex]\left\{\begin{array}{ccc}\dfrac{1}{3}x+\dfrac{1}{4}y=1&\text{multiply both sides by 12}\\2x-3y=-30\end{array}\right\\\left\{\begin{array}{ccc}12\!\!\!\!\!\diagup^4\cdot\dfrac{1}{3\!\!\!\!\diagup_1}x+12\!\!\!\!\!\diagup^3\cdot\dfrac{1}{4\!\!\!\!\diagup_1}y=12\cdot1\\2x-3y=-30\end{array}\right\\\left\{\begin{array}{ccc}4x+3y=12\\2x-3y=-30&\text{multiply both sides by (-2)}\end{array}\right\\\underline{+\left\{\begin{array}{ccc}4x+3y=12\\-4x+6y=60\end{array}\right}\qquad\text{add both sides of the equations}[/tex]
[tex].\qquad9y=72\qquad\text{divide both sides by 9}\\.\qquad y=8[/tex]
Answer:
8
Step-by-step explanation:
There are 8 people on the ballot for regional judges. Voters can vote for any 4. Voters can choose to vote for 0¸ 1¸ 2¸ 3¸ or 4 judges. In how many different ways can a person vote?
Answer:
163
Step-by-step explanation:
0 judges - [tex]C^8_0=1[/tex] way to vote
1 judge - [tex]C^8_1=8[/tex] ways to vote
2 judges-
[tex]C^8_2=\dfrac{8!}{2!(8-2)!}=\dfrac{6!\cdot 7\cdot 8}{2\cdot 6!}=\dfrac{56}{2}=28[/tex]
ways to vote for 2 different judges
3 judges-
[tex]C^8_3=\dfrac{8!}{3!(8-3)!}=\dfrac{5!\cdot 6\cdot 7\cdot 8}{2\cdot 3\cdot 5!}=\dfrac{6\cdot 56}{6}=56[/tex]
ways to vote for 3 different judges
4 judges-
[tex]C^8_4=\dfrac{8!}{4!(8-4)!}=\dfrac{4!\cdot 5\cdot 6\cdot 7\cdot 8}{4!\cdot 4!}=\dfrac{5\cdot 6\cdot 7\cdot 8}{2\cdot 3\cdot 4}=5\cdot 7\cdot 2=70[/tex]
ways to vote for 4 different judges
In total, there are
[tex]1+8+28+56+70=163[/tex]
different ways to vote.
What does x equal. 8, 9, or 10?
Answer:
x = 8
Step-by-step explanation:
We can see that this is using power of a point or PoP! So we immediately know that 5x = 4*10.
So solving for x (by dividing by 5 on both sides) we get:
x = 8
Answer : The value of 'x' is, 8
Step-by-step explanation :
According to the theorem, if two chords intersect inside a circle then the product of the lengths of the one chord equals to the length of another chord.
That means in the given figure,
AO × OB = CO × OD
Given:
Length AO = 10
Length OB = 4
Length CO = x
Length OD = 5
Now put all the given values in the above expression, we get:
AO × OB = CO × OD
10 × 4 = x × 5
40 = x × 5
x = 8
Therefore, the value of 'x' is, 8
Is the following relation a function? {(3, −5), (1, 2), (−1, −4), (−2, 2)}
Answer:
Function.
Step-by-step explanation:
A relation is a function every x that in your domain only gets assigned to exactly one number in your range.
Basically if you have a set of points and you see that the same x is being used more than once, then it isn't a function (unless for some reason they repeated the same point).
So the x's I see in the order that your points are is 3,1,-1,-2. All of these x's are different so it is a function.
Answer: Yes, it is a function.
Step-by-step explanation:
A relation is said to be a function, if each input value corresponds an unique output value.Usually we denote the input value as 'x' and the output value as 'y'.
The given relation: {(3, −5), (1, 2), (−1, −4), (−2, 2)}
Here , each input value corresponds an unique output value.
Therefore , the given relation is a function.
Which angles are corresponding angles with angle 8?
Answer:
[tex]\angle 12 \cong \angle 8\\\angle 4 \cong \angle 8[/tex]
Step-by-step explanation:
When two parallels lines are crossed by a transversal, certain pair of angles are called corresponding angles, specifically, those that are placed in the same side of the transversal, on inside the parallels and the other outside the parallels. The image attached shows an example of corresponding angles.
So, we observe in the given image that all corresponding angles with angle 8 are
[tex]\angle 12\\\angle 4[/tex]
These angles are form corresponding angle with [tex]\angle 8[/tex], that means they are congruent, that is
[tex]\angle 12 \cong \angle 8\\\angle 4 \cong \angle 8[/tex]
A = 1/2 d1d2 is the formula for the area of a _____ (1)
Answer:
C. Rhombus or Kite
Step-by-step explanation:
1/2 d1d2 is the formula for a rhombus or kite.
Answer:
Rhombus or Kite
Step-by-step explanation:
learning about it rn
The product of the slopes of perpendicular lines is always___
Answer:
-1
Step-by-step explanation:
The product of the slopes of perpendicular lines is always -1 .
Please help me simplify this fraction. Or is it already in its simplest form?
Answer:
1 / x^8
Step-by-step explanation:
We know that a^b / a^c = a^ (b-c)
x^7 / x^ 15 = x^ (7-15) = x^-8
We also that that a^-b = 1/ a^b
x^-8 = 1 / x^8
Answer:
1/(x^8)
Step-by-step explanation:
Simplify by the following steps. To make it easier, I will expand them:
First, expand each of the powers out:
[tex]\frac{x^7}{x^{15} } = \frac{x* x * x * x * x * x * x}{x * x * x * x * x * x * x * x * x * x * x * x * x * x * x}[/tex]
When dividing with the same variables with different powers, you are effectively subtracting the powers. Your answer will look like:
[tex]\frac{x^7}{x^(15)} = x^{7 - 15} = x^{-8}[/tex]
Next, simplify. Note that if there is a negative sign in the power, you must change the sign into a positive by flipping the fraction.
[tex]x^{-8} = \frac{1}{x^{8} }[/tex]
1/(x^8) is your answer.
~
The variable Z is directly proportional to X, and inversely proportional to Y. When X is 3 and Y is 19, Z has the value 0.94736842105263. What is the value of Z when X = 13, and Y = 26
Answer:
[tex]Z=2.99999999999995[/tex]
Step-by-step explanation:
We can write the proportionality equation as:
[tex]Z=k\frac{X}{Y}[/tex]
Note: Directly proportional goes top and top, multiplied. And inversely proportional goes top bottom, divided. Also, k is the proportionality constant.
When X is 3, Y is 19, Z is 0.94736842105263. Plugging these, we figure out k:
[tex]Z=\frac{kX}{Y}\\0.94736842105263=\frac{k(3)}{19}\\k=\frac{0.94736842105263*19}{3}\\k=5.99999999999999[/tex]
Now we put X = 13 and Y = 26 and k = 5.99999999999999, to find Z:
[tex]Z=\frac{kX}{Y}\\Z=\frac{(5.99999999999999)(13)}{26}\\Z=2.99999999999995[/tex]
what is the measure of Arc XY
The answer is A.
Because both angles of triangles are equal to 42° that means the distance of UV is equal to the distance of XY.
Hope this helps.
r3t40
Answer:
nope its actaually 46 degrees
Step-by-step explanation:
One number is seven less than another. Their sum is thirteen. Find the numbers.
(smaller value)
(larger value)
isn't there more than 1 possible combination here? how do i know which one it wants?
The numbers are 10 and 3.
Step-by-step explanation:
Set up equations relating the two numbers to each other.Solve for the two variables.STEP 1: Based on the problem, two equations can be set up:
First, "one number is seven less than another." This can be expressed mathematically:
Let x = first number
y = second number
[tex]x \ - 7 = \ y[/tex]
The second equation is based on "their sum is thirteen."
[tex]x \ + \ y \ = 13[/tex]
STEP 2: Solve for the variables.
In this step, substitute the value of y from Equation 1 into Equation 2:
[tex]x \ + \ (x \ - \ 7) \ = \ 13\\2x \ - \ 7 \ = 13\\[/tex]
Next, solve for x by manipulating the equation:
[tex]2x \ = \ 13 \ + \ 7\\2x \ = \ 20\\\boxed {x \ = \ 10}[/tex]
Now that the value of x is known, it can be used to determine the value of y.
To do this, use the calculated value for x and plug it into Equation 1:
[tex]y \ = \ x \ - 7\\y \ = 10 \ - 7\\\boxed {y = \ 3}[/tex]
Learn More
Learn more about system equations https://brainly.com/question/3056782Learn more about transposition https://brainly.com/question/260793Learn more about word problems https://brainly.com/question/11052962Keywords: two equations, two variables
To find the two numbers where one is seven less than the other and their sum is thirteen, a system of equations is set up and solved, revealing that the only possible combination is 10 (larger number) and 3 (smaller number).
To solve the problem where one number is seven less than another and their sum is thirteen, let's set up some equations.
Let x be the larger number and y be the smaller number. We can express the two conditions in the following way:
y = x - 7 (the smaller number is seven less than the larger number)
x + y = 13 (their sum is thirteen)
Substituting the first equation into the second gives us:
x + (x - 7) = 13
Simplifying, we get:
2x - 7 = 13
Adding 7 to both sides, we have:
2x = 20
Dividing both sides by 2, we find:
x = 10
Now we substitute x back into the first equation to find y:
y = 10 - 7
y = 3
So the larger number is 10 and the smaller number is 3. There is only one possible combination of numbers that fit the given conditions.
The function f(x) = x2 + 22x + 58 is translated 4 units to the right and 16 units up. What is the vertex form of the new function? (x – 11)2 + 58 (x + 22)2 – 121 (x + 7)2 – 47 (x – 15)2 + 94
Answer:
The new function is (x + 7)² - 47 ⇒ the 3rd answer
Step-by-step explanation:
* Lets put the function f(x) in the vertex form at first and then make
the translation
∵ The general form of the quadratic function is
f(x) = ax² + bx + c
∵ The x-coordinate of the vertex of the function is -b/2a
∵ The y-coordinate of the vertex of the function is f(-b/2a)
- Lets find a , b from the function two find the vertex point
∵ f(x) = x² + 22x + 58
∴ a = 1 , b = 22 , c = 58
∵ x-coordinate of the vertex = -b/2a
∴ x-coordinate of the vertex = -22/2(1) = -11
∵ y-coordinate of the vertex = f(-11)
∴ f(-11) = (-11)² + 22(-11) + 58 = 121 - 242 + 58 = -63
∴ The vertex point is (-11 , -63)
- The vertex form of the quadratic function is f(x) = (x - h)² + k , where
(h , k) are the coordinates of the vertex point
∵ The vertex point is (-11 , -63)
∴ h = -11 , k = -63
∴ f(x) = (x - -11)² + -63
∴ f(x) = (x + 11)² - 63
* lets revise the rules of the translation
- If the function f(x) translated horizontally to the right
by m units, then the new function g(x) = f(x - m)
- If the function f(x) translated horizontally to the left
by m units, then the new function g(x) = f(x + m)
- If the function f(x) translated vertically up
by n units, then the new function g(x) = f(x) + n
- If the function f(x) translated vertically down
by n units, then the new function g(x) = f(x) – n
∵ f(x) will translate 4 units to the right
∴ m = 4
∵ f(x) ⇒ f(x - m)
∴ (x + 11)² ⇒ (x + 11 - 4)² = (x + 7)²
∵f(x) will translate 16 units up
∴ -63 will add by 16
∴ n = 16
∴ f(x) ⇒ f(x) + n
∵ -63 + 16 = -47
∴ The new function is (x + 7)² - 47
Answer:
(x + 7)^2 - 47
Step-by-step explanation:
just answered this on my class
write the expression as the sine or cosine of an angle sin(pi/7) cos(x) + cos(pi/7) sin(x)
Answer:
[tex]\sin(\frac{\pi}{7}+x)[/tex]
Step-by-step explanation:
We are going to use the identity
[tex]\sin(a+b)=\sin(a)\cos(b)+\cos(a)\sin(b)[/tex]
because this identities right hand side matches your expression where
[tex]a=\frac{\pi}{7}[/tex] and [tex]b=x[/tex].
So we have that [tex]\sin(\frac{\pi}{7})\cos(x)+\cos(\frac{\pi}{7})\sin(x)[/tex] is equal to [tex]\sin(\frac{\pi}{7}+x)[/tex].
The given expression is written as sin(π/7 + x). Using sine of compound angle identity it is obtained.
What are compound angle identities for sine and cosine?A compound angle is the sum of two or more angles. Consider A and B are two angles. Where their compound angle becomes A + B. So, the sine and cosine of this compound angle are
1) sin (A + B) = sin A cos B + cos A sin B
2) sin (A - B) = sin A cos B - cos A sin B
3) cos (A + B) = cos A cos B - sin A sin B
4) cos (A - B) = cos A cos B + sin A sin B
Calculation:The given expression is sin(π/7) cos(x) + cos(π/7) sin(x)
This is in the form of sin A cos B + cos A sin B
where A = π/7 and B = x
So, using the above identity we can write,
sin(π/7) cos(x) + cos(π/7) sin(x) = sin(π/7 + x)
Thus, the given expression is expressed in the angle of sine. I.e., sin(π/7 + x).
Learn more about trigonometric identities here:
https://brainly.com/question/10391668
#SPJ2
If f(x) = 7 + 4x and g(x)= 7x, what is the value of (f/g)(5)
Answer:
27/35
Step-by-step explanation:
(f/g)(5) means f(5)/g(5).
So we will need to find both f(5) and g(5).
f(5) means replace x with 5 in f. This gives us 7+4×5.
Let's simplify 7+4×5:
7+4×5
7+20
27.
g(5) means replace x with 5 in g. This gives us 7×5.
Simplifying 7×5 gives us 35.
(f/g)(5)=f(5)/g(5)=27/35.
The figure below is a right rectangular prism with
rectangle ABCD as its base.
What is the area of the base of the rectangular prism?
•square centimeters
What is the height of the rectangular prism?
•centimeters
What is the volume of the rectangular prism?
•cubic centimeters
Answer:
Part 1) The area of the base of the rectangular prism is [tex]18\ cm^{2}[/tex]
Part 2) The height of the rectangular prism is equal to [tex]6\ cm[/tex]
Part 3) The volume of the rectangular prism is [tex]108\ cm^{3}[/tex]
Step-by-step explanation:
Part 1) What is the area of the base of the rectangular prism?
we know that
The base of the rectangular prism is the rectangle ABCD
so
AD=BC and AB=DC
The area B of the rectangle is equal to
[tex]B=AD*DC[/tex]
substitute
[tex]B=(9)(2)=18\ cm^{2}[/tex]
Part 2) What is the height of the rectangular prism?
The height of the rectangular prism is equal to the segment line AW (segment perpendicular to the base)
we have that
[tex]H=AW=BX=DY=CZ=6\ cm[/tex]
Part 3) What is the volume of the rectangular prism?
we know that
The volume of the rectangular prism is equal to
[tex]V=BH[/tex]
where
B is the area of the base of the prism
H is the height of the prism
we have
[tex]B=18\ cm^{2}[/tex]
[tex]H=6\ cm[/tex]
substitute
[tex]V=(18)(6)=108\ cm^{3}[/tex]
The area of the base of the rectangular prism is 18 cm² and its volume is 108 cm³.
PrismPrism is a three dimensional shape with two identical shapes called bases facing each other.
From the diagram:
Length = 9 cm, width = 2 cm and height = 6 cmArea of base = length * width = 9 cm * 2 cm = 18 cm²
Volume = height * length * width = 6 * 9 * 2 = 108 cm³
The area of the base of the rectangular prism is 18 cm² and its volume is 108 cm³.
Find out more on prism at: https://brainly.com/question/23963432
A can factory requires 2 sheets of metal to make 36 cans and 10 sheets of metal to make 180 cans. The proportionality constant between the number of cans made and the number of sheets of metal used is .
Divide the number of cans by the number of sheets to find the constant.
36 cans / 2 sheets = 18 cans per sheet.
180 cans / 10 sheets = 18 cans per sheet.
The proportionality constant is 18 cans per sheet.
ANSWER AND I WILL DO YOU A FAVOR!!!!
the temperature of a chemical solution is originally 21 Celsius. A chemist heats the solution at a constant rate, and the temperature of the solution is 75 Celsius after 12 minutes of heating.
Temperature, T, of the solution in Celsius is a function of X, the heating time in minutes
Write the function’s formula.
T=____
Since m = 4.5 and b = 21 the desired formula is:
T=4.5x+21
if N=b/d(squared) write down in terms of b and d
a.the square of N
b.the square root of N
c.the reciprocal of N
which paper folding method can be used to form the midpoint of a line segment
Hi !
Answer:
Begin with a line segment on the paper and fold the paper so that the segment's endpoints lie on top of each other.
The method used in paper folding to form the midpoint of a line segment is called bisecting a line segment. This involves drawing the line segment, folding the paper so the endpoints of the line segment meet, and marking the point of intersection which forms the midpoint.
Explanation:The method that can be used in paper folding to form the midpoint of a line segment is called bisecting a line segment. Here's how you can do it:
Draw the line segment on a piece of paper.Fold the paper so that the endpoints of the line segment meet. Ensure the fold is sharp and precise.The fold line will intersect the line segment at its midpoint. You can mark this point for clarity.That point of intersection is the midpoint of the line segment. You've now bisected the line segment into two equal halves using paper folding.
Learn more about bisecting a line segmenthttps://brainly.com/question/2598457
#SPJ11
what is the value of 3x to the second power + 4y to the second power if x=2 and y=-3?
Answer: 3(2)^2 + 4(3)^2
Step-by-step explanation:
First do what is replacing the variables by changing X to 2 and Y to -3
3(2)^2 + 4(-3)^2 = 3(4) + 4(9) = 12 + 36 = 48
Answer: The value is 48
Step-by-step explanation:
Given the following expression:
[tex]3x^2+4y^2[/tex]
You need to substitute the values of each variables provided in the exercise into this expression. You can observe that the value of the variable "x" and the value of the variable "y" are:
[tex]x=2 \\ y=-3[/tex]
Therefore, substituting values, you get:
[tex]3x^2+4y^2=3(2)^2+4(-3)^2=3(4)+4(9)=12+36=48[/tex]
Find the radius of a circle with an area of 90 inches.
Answer:
r = 5.35
Step-by-step explanation:
The radius of a circle with an area of 90 inches is 5.35.
Use the formula: A=πr2
r=A
π=90
π≈5.35237
One fifth of the square of a number
Answer: 0.2
Explainations: 1/5 = 0.2
Answer:
Number would be [tex]\frac{x^{2}}{5}[/tex].
Step-by-step explanation:
Given : One fifth of the square of a number.
To find : Expression .
Solution ; We have given One fifth of the square of a number.
According to question :
Let the number = x .
Square of the number = x².
One fifth of the square of the number = [tex]\frac{x^{2}}{5}[/tex].
Therefore, Number would be [tex]\frac{x^{2}}{5}[/tex].
The motion of a weight that hangs from a spring is represented by the equation h=-5sin(3pi/4 t) . It models the weight’s height, h, in inches above or below the rest position as a function of time, t, in seconds. Approximately when will the object be 4 inches below the rest position? Round to the nearest hundredth, if necessary. 0 seconds 0.29 seconds 0.39 seconds 1.95 seconds
Answer:
The answer on edge is C: 0.39 seconds.
Step-by-step explanation:
At t = 0.39 seconds the object is 4 inches below the rest position option third is correct.
What is sin function?It is defined as the function which is sinusoidal in nature, and it has a domain of all real numbers and lies between the [a, a]where is a amplitude of the function.
We have:
The motion of a weight that hangs from a spring is represented by the equation:
h = -5sin[(3π/4)t]
Plug h = -4
-4 = -5sin[(3π/4)t]
Or
-4 = -5sin[135t]
135t = 53.13
t = 0.39 seconds
Thus, at t = 0.39 seconds the object is 4 inches below the rest position option third is correct.
Learn more about the sin function here:
https://brainly.com/question/14397255
#SPJ2
Which term describes a line segment that connects a vertex of a triangle to a
point on the line containing the opposite side, so that the line segment is
perpendicular to that line?
A. Altitude
B. Median
C. Perpendicular bisector
D. Angle bisector
Answer:
A. AltitudeStep-by-step explanation:
It's the definition of an altitude.
Answer: Altitude
Step-by-step explanation:
If point b(6,4) undergoes the following translation (x-8,y+2) what are the coordinates of point b’
Answer:
(-2,6)
Step-by-step explanation:
If b is (6,4) and we have b' is the image that follows from the translation
(x-8,y+2).
Basically the image of (x,y) is (x-8,y+2).
So the image of (6,4) is (6-8,4+2).
Simplify:
(6-8,4+2)
(-2,6).
b' is (-2,6).
If f(x) = 3^+ 10 and g(x) = 2x - 4, find (f - g)(x).
Answer:
3^x -2x +14
Step-by-step explanation:
I will assume you mean 3^x in the function f(x)
f(x) = 3^x+ 10
g(x) = 2x - 4
(f - g)(x) = 3^x+ 10 - (2x - 4)
Distribute the minus sign
= 3^x+ 10 - 2x + 4
= 3^x -2x +14
2x)(x2) + (2x)(x) + (2x)(-2) + (3)(x2) + (3)(x) + (3)(-2)
Answer:
6x^2+2x-6
Step-by-step explanation:
In the expression (2x)(x2)+(2x)(x)+(2x)(-2)+(3)(x2)+(3)(-2) take each set of two and solve those individually. The expression then becomes 4x^2+2x^2-4x+6x-6 the combining like terms you get 6x^2+2x-6.